Development of a mathematical model for hydrothermal carbonization of biomass: Comparison of experimental measurements with model predictions. (1st January 2021) - Heidari, Mohammad; Salaudeen, Shakirudeen; Arku, Precious; Acharya, Bishnu; Tasnim, Syeda; Dutta, Animesh
Abstract: The present study aims to develop a mathematical model for hydrothermal carbonization (HTC) by incorporating heat transfer rate, reaction kinetics, and the porous structure of the biomass for the first time using various modules of COMSOL Multiphysics software. HTC experiments on pine wood particles using a batch reactor were performed to calibrate the model. Operating parameters such as temperature, residence time, biomass to water ratio, and power consumption were recorded, and the obtained products were characterized via ultimate analysis, and bomb calorimetry experiments. Experimental results validate the predictions of the developed model. It is observed that the predicted energy consumption was considerably deflected from the experimental value when the reactions during the processing and porosity of biomass were not considered. Hence, the developed model can potentially be used as a first step in designing an industrial reactor for hydrothermal conversion of biomass, which may attract investors and policy makers for commercialization of this technology. Highlights: A model of HTC considering reaction heat and porosity is presented. Experimental results validate the predictions of the developed model. Without considering reaction heat and porosity, the models are not accurate.